A Review of Performance of Legal Deposit Centre in Uganda : Case studies of National Library of Uganda, Uganda Management Institute of Uganda, Makerere University Africana Section - Kyomugisha, Agnes (Kampala : Uganda Christian University, 2010)
Descriptive Cataloguing Dissertation (MHRME) Uganda Christian University Mukono.
Includes bibliographical references and appendix
Keywords: Legal deposit centres -- Uganda